Pathological Characteristics of a Patient with Severe Fever with Thrombocytopenia Syndrome (SFTS) Infected with SFTS Virus through a Sick Cat’s Bite - Tsuru, Masatoshi; Suzuki, Tadaki; Murakami, Tomoyuki; Matsui, Kumiko; Maeda, Yuuji; Yoshikawa, Tomoki; Kurosu, Takeshi; Shimojima, Masayuki; Shimada, Tomome; Hasegawa, Hideki; Maeda, Ken; Morikawa, Shigeru; et al. (Viruses, 2021)
A woman in her fifties showed symptoms of fever, loss of appetite, vomiting, and general fatigue 2 days after she was bitten by a sick cat, which had later died, in Yamaguchi prefecture, western Japan, in June 2016. She subsequently died of multiorgan failure, and an autopsy was performed to determine the cause of death. However, the etiological pathogens were not quickly identified. The pathological features of the patient were retrospectively re-examined, and the pathology of the regional lymph node at the site of the cat bite was found to show necrotizing lymphadenitis with hemophagocytosis. The pathological features were noted to be similar to those of patients reported to have severe fever with thrombocytopenia syndrome (SFTS). Therefore, the lymph node section was retrospectively tested immunohistochemically, revealing the presence of the SFTS virus (SFTSV) antigen. The sick cat showed similar symptoms and laboratory findings similar to those shown in human SFTS cases. The patient had no history of tick bites, and did not have skin lesions suggestive of these. She had not undertaken any outdoor activities. It is highly possible that the patient was infected with SFTSV through the sick cat’s bite. If a patient gets sick in an SFTS-endemic region after being bitten by a cat, SFTS should be considered in the differential diagnosis.